William Simmonds the silent heart of the arts and crafts movement - Douglas-Home, Jessica 1944- (Unicorn, 2018)
This book looks at the Arts & Crafts movement through the work of William Simmonds, his life, his friends and their attitudes to modernism to show why that movement was important, how it fitted into its age and what it taught then and can teach us today